Militarised Safety: Politics of Exclusion - Ayesha Sarfraz; Arsalan Rafique (Footprint)
Warfare and armed conflict have evolved radically with the advent of technology and perhaps most importantly, with globalization. Unlike the West, which has come to terms with violence through constant memorialization, multidisciplinary discourse and legislature, cities in the developing world lack audible intellectual trajectories. Therefore, studies on the merits of the non-Western conditions of conflict must take into account the complex structures of organization of society, politics, religion and ethnicities, as a result of the globalization of violence. Developing and less politically stable countries like Pakistan, on the other hand, are losing urban space through attacks from the perpetrators and yet more so from the state as the literal subtraction of the public realm gets framed as security measures Whereas international law states that during times of war, civilian rights can be legally suspended - in Pakistan that suspension has shifted into a state of temporariness without prescribed limits. This paper looks at urban space in the developing world as a dual site of the threat and the threatened while questioning the effectivity of security apparatus that have become the foundations for design of the contemporary city.